A new Elf5CreERT2‐GFP BAC transgenic mouse model for tracing Elf5 cell lineages in adult tissues. Issue 10 (1st May 2019) - Singh, Snahlata; Elenio, Emily; Leu, Nicolae A.; Romano, Rose‐Anne; Vaughan, Andrew E.; DeRiso, Jennifer; Surendran, Kameswaran; Chakrabarti, Rumela
Abstract : Elf5 is a transcription factor known to regulate critical developmental processes and has been shown to act as a tumour suppressor in multiple cancers. Elf5 knockout mice are embryonically lethal, limiting in vivo studies pertaining to its function. Moreover, haploinsufficiency of Elf5 limits the use of current mouse models to investigate adult tissue distribution of Elf5. Here, we successfully generated Elf5 Cre ERT 2‐ GFP bacterial artificial chromosome (BAC) transgenic mice and show that Elf5 + cells are present in several adult tissues, where its expression was previously not known. Our study demonstrates the unique distribution of Elf5 + cells in multiple adult organs, which will facilitate future studies investigating the function of Elf5 in these tissues during homeostasis, repair and cancer. Abstract :